Unraveling the Potential of SGK1 in Osteoporosis: From Molecular Mechanisms to Therapeutic Targets - Fei Yang; Changshun Chen; Rongjin Chen; Chenghui Yang; Zirui Liu; Lei Wen; Hefang Xiao; Bin Geng; Yayi Xia (Biomolecules)
Osteoporosis (OP) is a prevalent metabolic bone disease, with several million cases of fractures resulting from osteoporosis worldwide each year. This phenomenon contributes to a substantial increase in direct medical expenditures and poses a considerable socioeconomic burden. Despite its prevalence, our understanding of the underlying mechanisms remains limited. Recent studies have demonstrated the involvement of serum glucocorticoid-regulated protein kinase 1 (SGK1) in multiple signaling pathways that regulate bone metabolism and its significant role in the development of osteoporosis. Therefore, it is of great significance to deeply explore the mechanism of SGK1 in osteoporosis and its therapeutic potential. In this paper, we present a comprehensive review of the structure and activation mechanism of SGK1, its biological function, the role of SGK1 in different types of osteoporosis, and the inhibitors of SGK1. The aim is to comprehensively assess the latest research progress with regards to SGK1’s role in osteoporosis, clarify its role in the regulation of bone metabolism and its potential as a therapeutic target, and lay the foundation for the development of novel therapeutic strategies and personalized treatment in the future. Furthermore, by thoroughly examining the interactions between SGK1 and other molecules or signaling pathways, potential biomarkers may be identified, thereby enhancing the efficacy of early screening and intervention for osteoporosis.